2014
DOI: 10.1038/bjc.2014.124
|View full text |Cite
|
Sign up to set email alerts
|

GOLPH3 is a novel marker of poor prognosis and a potential therapeutic target in human renal cell carcinoma

Abstract: Background:Golgi phosphoprotein 3 (GOLPH3) has been reported to be involved in the development of several human cancers. The present study was conducted to investigate the expression of GOLPH3 and its prognostic significance in renal cell carcinoma (RCC). Meanwhile, the function of GOLPH3 in human RCC was further investigated in cell culture models.Methods:Expression of GOLPH3 was examined in 43 fresh RCC tissues and paired adjacent normal renal tissues by real-time quantitative PCR and western blotting. Immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 32 publications
7
24
0
Order By: Relevance
“…The results revealed that depletion of GOLPH3 significantly suppressed tumor growth in the nude mice. Consistent with our finding, Xue et al demonstrated that GOLPH3 knockdown inhibited the tumorigenicity of cancer cells in a xenograft mouse model ( 25 ). Further analysis of the grafted tumors verified that GOLPH3 downregulation was associated with a reduction in c-Myc and hTERT expression, as well as reduced telomerase activity, in the GOLPH3-suppressed group compared with that in the vector group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results revealed that depletion of GOLPH3 significantly suppressed tumor growth in the nude mice. Consistent with our finding, Xue et al demonstrated that GOLPH3 knockdown inhibited the tumorigenicity of cancer cells in a xenograft mouse model ( 25 ). Further analysis of the grafted tumors verified that GOLPH3 downregulation was associated with a reduction in c-Myc and hTERT expression, as well as reduced telomerase activity, in the GOLPH3-suppressed group compared with that in the vector group.…”
Section: Discussionsupporting
confidence: 93%
“…The percentage of stained tumor cells was classified into 4 grades (0, no positive tumor cells; 1, <10% positive tumor cells; 2, 10–35% positive tumor cells; 3, 35–70% positive tumor cells; 4, >70% positive tumor cells); while the cell staining intensity was classified into 4 levels (0–3+) (0, no staining; 1, weak staining or light yellow; 2, moderate staining or yellow brown; 3, strong staining or brown color). The two values were multiplied to obtain the IHC score (staining index, SI), giving SI values of 0, 1, 2, 3, 4, 6, 8, 9, 12, as previously described ( 25 ). The optimal cutoff values were SI ≥ 6 to define tumors with high GOLPH3 or STIP1 expression, and SI ≤ 4 to define tumors with low GOLPH3 expression.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, DFS of patients with NSCLC and high GOLPH3 overexpression was poorer compared with that of patients with NSCLC and low GOLPH3 expression. Subsequently, we found that GOLPH3 expression in NSCLC was notably Previous studies revealed that GOLPH3 is closely related to the occurrence and development of malignant solid tumours, such as renal, ovarian, breast, and oesophageal cancers [17][18][19][20]. To our knowledge, this study is the first to indicate an association between GOLPH3 positivity in patients with NSCLC and poor prognosis and to suggest that GOLPH3 expression may be an independent prognostic factor for patients with NSCLC.…”
Section: Discussionsupporting
confidence: 53%
“…Evidence of transformation by overexpression of GOLPH3 has been reported in MDA-MB-231 and MCF7 breast cancer cell lines (911), and U251 and U87 glioblastoma cell lines (12, 13). Frequent overexpression of GOLPH3 and correlation with poor prognosis have been reported in multiple tumor types including 58–72% of non-small cell lung cancers (14, 15), 52% of breast cancers (11), 70% of prostate cancers (16), 73% of pancreatic ductal adenocarcinomas (17), 65% of hepatocellular carcinomas (18, 19), 55–58% of gastric cancers (20, 21), 53% of renal cell carcinomas (22), 41–53% of glioblastomas (12, 23, 24), 49% of esophageal squamous carcinomas (25), and 45% of ovarian carcinomas (26, 27). Overexpression of GOLPH3 occurs frequently in rhabdomyosarcoma, and knockdown of GOLPH3 in rhabdomyosarcoma cell lines impairs cell proliferation (28).…”
Section: Golph3 Is An Oncogenementioning
confidence: 99%